Endothelial Aryl Hydrocarbon Receptor Nuclear Translocator Mediates the Angiogenic Response to Peripheral Ischemia in Mice With Type 2 Diabetes Mellitus - Nguyen, Tu; Zheng, Mei; Knapp, Maura; Sladojevic, Nikola; Zhang, Qin; Ai, Lizhuo; Harrison, Devin; Chen, Anna; Sitikov, Albert; Shen, Le; Gonzalez, Frank J.; Zhao, Qiong; et al. (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia-inducible factors (HIFs) are the master regulators of angiogenesis, a process that is impaired in patients with diabetes mellitus (DM). The transcription factor aryl hydrocarbon receptor nuclear translocator (ARNT, also known as HIF1β) has been implicated in the development and progression of diabetes. Angiogenesis is driven primarily by endothelial cells (ECs), but both global and EC-specific loss of ARNT-cause are associated with embryonic lethality. Thus, we conducted experiments in a line of mice carrying an inducible, EC-specific ARNT-knockout mutation (ArntΔEC, ERT2) to determine whether aberrations in ARNT expression might contribute to the vascular deficiencies associated with diabetes. Mice were first fed with a high-fat diet to induce diabetes. ArntΔEC, ERT2 mice were then adminstrated with oral tamoxifen to disrupt Arnt and peripheral angiogenesis was evaluated by using laser-Doppler perfusion imaging to monitor blood flow after hindlimb ischemia. The ArntΔEC, ERT2 mice had impaired blood flow recovery under both non-diabetic and diabetic conditions, but the degree of impairment was greater in diabetic animals. In addition, siRNA-mediated knockdown of ARNT activity reduced measurements of tube formation, and cell viability in human umbilical vein endothelial cells (HUVECs) cultured under high-glucose conditions. The ArntΔEC, ERT2 mutation also reduced measures of cell viability, while increasing the production of reactive oxygen species (ROS) in microvascular endothelial cells (MVECs) isolated from mouse skeletal muscle, and the viability of ArntΔEC, ERT2 MVECs under high-glucose concentrations increased when the cells were treated with an ROS inhibitor. Collectively, these observations suggest that declines in endothelial ARNT expression contribute to the suppressed angiogenic phenotype in diabetic mice, and that the cytoprotective effect of ARNT expression in ECs is at least partially mediated by declines in ROS production.